Ways to Develop Innovative Banking Services in Uzbekistan - Nurmuxammedov Abdijabbar Yunusovich (Miasto Przyszłości, 2024)
This article discusses the internal and external factors influencing the development of innovative banking services in the Republic of Uzbekistan. The problems of the development of remote banking services are highlighted here and author's approaches to their solution are proposed.